Investigation of hypocholesterinemic properties of rape and sunflower lecitines - N. N. Kornen; S. A. Kalmanovich; T. A. Shakhray; E. V. Kuzminova; M. P. Semenenko (Новые технологии)
The data characterizing the effectiveness of hypocholesteronemic action of rapeseed and sunflower lecithins in experiments on laboratory animals are prsented. It has been established that rapeseed and sunflower lecithins exhibit hypocholesteronemic properties. It has been found that the degree of reduction in the mass fraction of total cholesterol and low-density lipoprotein cholesterol in the blood serum of animals of the experimental group that received cholesterol + rapeseed lecithins in addition to the usual diet is higher compared to this index reduction in the blood serum of the animals of the experimental group that received, cholesterol + sunflower lecithins in addition to the usual ration.